An Assessment of Treated Municipal Wastewater Used for Irrigation of Grapevines with Respect to Water Quality and Nutrient Load : Assessment of TMW for vineyard irrigation - Howell, C. L.; Hoogendijk, K.; Myburgh, P.A.; Lategan, E. L. (South African Journal of Enology and Viticulture, 2022)
The impact of treated municipal wastewater (TMW) irrigation on soil and grapevines was assessed under field conditions in vineyards in the Coastal region of South Africa. Grapevines were irrigated using TMW from the City of Cape Town uninterruptedly over a period of 11 years. Grapevines were either rain fed, irrigated with TMW via a single dripper line, or received twice the volume via double dripper lines. The quality of the TMW used for vineyard irrigation was acceptable, and below the minimum criteria stipulated by the General Authorisations to irrigate up to 500 m3 per day in terms of pH, ECw and SAR. Mean Na+ concentration in the TMW exceeded the critical value of 100 mg/ℓ for irrigating grapevines in South Africa. The Cl- levels in the TMW were well below the threshold value of 700 mg/ℓ at which toxicity in grapevines might occur. Consistently high P concentrations measured in the TMW could lead to the formation of algal blooms in water storage facilities and bio-fouling of irrigation equipment. The low N content in the TMW could not supply the annual N requirement of grapevines. The annual amount of P applied via the single dripper lines was slightly below grapevine requirements, whereas double the TMW irrigation applied excessive amounts of P. Amounts of K+ applied via TMW irrigation was in excess of annual grapevine requirements, which could affect wine quality negatively. The amount of Ca2+ and Mg2+ applied via the TMW also exceeded annual grapevine requirements.